Hydrothermal synthesis and crystal structure of catena-poly[(1,10-phenanthroline-κ 2 N,N′)-bis(μ 2-nitroisophthalato-κ 3 O,O′:O″)nickel(II)], C20H13NiN3O7 - Wen-Jie Bi; Dong Xie; Xing-ming Hu; Hu Chen; He-dong Bian (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C20H13NiN3O7; triclinic, P1̄ (no. 2), a = 8.329(7) Å, b = 8.726(8) Å, c = 13.300(12) Å, α = 85.948(14)°, β = 75.509(14)°, γ = 72.258(13)°, V = 891.3(13) Å3, Z = 2, R gt(F) = 0.0373, wR ref(F 2) = 0.1007, T = 296(2) K.